Tips for Finding Unusual Allies and Building Innovative Alliances - and Jacobstein, David (2018)
One of the truisms of thinking and working politically (TWP) is that it requires looking differently at how stakeholders relate to a given development challenge or process, and building coalitions of the “right actors at the right time” who can drive forward progress while working with the grain of the context. While it’s easy to call for coalitions for change and diverse stakeholder engagement, identifying allies beyond those already seized with an issue, and finding ways to collaborate with stakeholders who may have different reasons for joining a coalition, is a challenging task. These are some suggested tips to improve working in that fashion.